2017
DOI: 10.1128/jcm.02248-16
|View full text |Cite
|
Sign up to set email alerts
|

Towards a New Strategy for Diagnosis of Congenital Trypanosoma cruzi Infection

Abstract: The immigration of Latin American women of childbearing age has spread the congenital transmission of Chagas disease to areas of nonendemicity, and the disease is now a worldwide problem. Some European health authorities have implemented screening programs to prevent vertical transmission, but the lack of a uniform protocol calls for the urgent establishment of a new strategy common to all laboratories. Our aims were to (i) analyze the trend of passive IgG antibodies in the newborn by means of five serological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
19
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 59 publications
1
19
0
1
Order By: Relevance
“…Because of the lack of a single reference standard test, the possibility of cross-reactivity, and the biological diversity and genetic polymorphism of T. cruzi , which is due to the existence of six discrete typing units (DTUs) of the parasite in different geographical areas [ 10 ] , the WHO recommends that a diagnosis of chronic CD be based on two positive results obtained using two different methods: a conventional test followed by a non-conventional assay [ 9 ]. Serological diagnosis remains a challenge and screening schemes have been implemented only recently, mainly for blood and organ donors, pregnant women, and newborns [ 11 13 ], in an effort to control the transmission of CD [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Because of the lack of a single reference standard test, the possibility of cross-reactivity, and the biological diversity and genetic polymorphism of T. cruzi , which is due to the existence of six discrete typing units (DTUs) of the parasite in different geographical areas [ 10 ] , the WHO recommends that a diagnosis of chronic CD be based on two positive results obtained using two different methods: a conventional test followed by a non-conventional assay [ 9 ]. Serological diagnosis remains a challenge and screening schemes have been implemented only recently, mainly for blood and organ donors, pregnant women, and newborns [ 11 13 ], in an effort to control the transmission of CD [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…The use of light microscopy to detect parasitic forms of T. cruzi is recommended in cases in which there are clinical or epidemiological suspicions of an acute phase, since a greater amount of trypomastigotes circulating in blood can be observed during the first weeks after infection (Vega and Náquira, 2006;Abras et al, 2017). The puppy found to be positive using light microscopy and PCR in the transversal study, in which antibodies against the agent or clinical signs were not found, indicates that the puppy had been recently infected and was in an acute phase of infection.…”
Section: Discussionmentioning
confidence: 99%
“…The finding of a PCR-positive dog in May 2016 in the longitudinal study with enlarged popliteal lymph nodes and which was found in the following examination to be PCR-negative but serologically positive, indicates that the dog was possibly ending the acute phase in May, and by the time of the next examination had entered to the indeterminate phase. This phase is characterized by a reduction of parasitemia due to intracellular infection of cardiac cells, where the parasite continues replicating itself for many years without causing evident clinical signs (Vega and Náquira, 2006;Abras et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, serological diagnosis has certain disadvantages: the persistence of positive results in chronically infected patients for years after treatment [ 20 ], the possibility of cross-reactions with other trypanosomatids like Trypanosoma rangeli or Leishmania spp. [ 21 ], and the transmission of passive antibodies from mother to newborn [ 22 24 ].…”
Section: Introductionmentioning
confidence: 99%